Check list of the Dryopidae, Elmidae and Hydraenidae (Coleoptera) of Greece - Jach, Μ. Α.; Avtzis, Ν. D. (ENTOMOLOGIA HELLENICA, 1998)
Information on the Greek water beetle families Dryopidae, Elmidae and Hydracnidae is fairly scattered throughout the literature. Our knowledge of these families which inhabit mainly running water largely results from numerous short excursions, collecting trips and limnological projects carried out by numerous European entomologists (e.g. P. Audisio, G. Ferro, M.A. Bch, E. Janssens, H. Malicky, A. d’Orchymont, F. Wachtel). However, a concise summary of the Dryopidae, Elmidae and Hydraenidae known from Greece has never been published. This survey is mainly based on literature records. However, a number of species which were recently collected in Greece are recorded for the first time from that country. In the following check list, the names of the species (or subspecies) are followed by the name(s) of the authors) and by one important reference which contains information about the species distribution in Greece. Ten species are herein recorded from Greece for the first time.